Genetics And Environmental Regulation Of Shigella Iron Transport Systems - Wyckoff, Elizabeth E. (2009)
Shigella spp . have transport systems for both ferric and ferrous iron. The iron can be taken up as free iron or complexed to a variety of carriers. All Shigella species have both the Feo and Sit systems for acquisition of ferrous iron, and all have at least one siderophore-mediated system for transport of ferric iron. Several of the transport systems, including Sit, Iuc/IutA (aerobactin synthesis and transport), Fec (ferric di-citrate uptake), and Shu (heme transport) are encoded within pathogenicity islands. The presence and the genomic locations of these islands vary considerably among the Shigella species, and even between isolates of the same species. The expression of the iron transport systems is influenced by the concentration of iron and by environmental conditions including the level of oxygen. ArcA and FNR regulate iron transport gene expression as a function of oxygen tension, with the sit and iuc promoters being highly expressed in aerobic conditions, while the feo ferrous iron transporter promoter is most active under anaerobic conditions. The effects of oxygen are also seen in infection of cultured cells by Shigella flexneri; the Sit and Iuc systems support plaque formation under aerobic conditions, whereas Feo allows plaque formation anaerobically.